1990
DOI: 10.1111/j.1749-6632.1990.tb37670.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of P1‐ and P2‐Purinoceptors

Abstract: INTRODUCTIONIn 1978, Burnstock' proposed a system for the classification of the receptors at which adenosine and adenine nucleotides act to produce their diverse and numerous effects. This proposal was based on a review of the extensive literature concerning the actions of purine nucleosides and nucleotides on a wide variety of tissues. This classification system termed the receptors at which the purine nucleosides and nucleotides act purinoceptors and proposed that there were two major subtypes, the PI-and P,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

1994
1994
2001
2001

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…On the other hand, the absence of any effect by ADP, AMP or adenosine injected into the SON on the urine outflow suggests that the effects of ATP are mediat ed mainly through an activation of P2-purinoceptors (11,18,19). These results also contrasts with those observed in the PVN, in which microinjection of ATP causes a more potent antidiuretic effect than that of adenosine and is not antagonized by theophylline (14).…”
Section: Discussioncontrasting
confidence: 55%
“…On the other hand, the absence of any effect by ADP, AMP or adenosine injected into the SON on the urine outflow suggests that the effects of ATP are mediat ed mainly through an activation of P2-purinoceptors (11,18,19). These results also contrasts with those observed in the PVN, in which microinjection of ATP causes a more potent antidiuretic effect than that of adenosine and is not antagonized by theophylline (14).…”
Section: Discussioncontrasting
confidence: 55%
“…A, receptors are present on the vascular endothelial cells, stimulate adenylate cyclase, and mediate the vasodilator effects of adenosine (21). P2 receptors are also classified into P2,, P2,, P,,, and P2, receptors (21). The relative predominance of these receptors on the cell varies between different organs, with P2, receptors being more predominant on vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Based on receptor affinity and ligand binding studies, PI receptors have been further classified into A, and A, subtypes; A, receptors inhibit adenylate cyclase and appear predominantly in the heart, where they mediate the negative chronotropic and inotropic effects of adenosine (21). A, receptors are present on the vascular endothelial cells, stimulate adenylate cyclase, and mediate the vasodilator effects of adenosine (21). P2 receptors are also classified into P2,, P2,, P,,, and P2, receptors (21).…”
Section: Discussionmentioning
confidence: 99%
“…Despite such difficulties, ATP (P 2 purinergic) receptors and adenosine (P 1 purinergic; also known as A 1 -A 3 ) receptors have been distinguished from each other based on the relative potency of various nucleoside and nucleotide agonists and by the differential actions of a limited and somewhat nonselective collection of antagonists (Burnstock 1978, Paton & Taerum 1990. Using similar criteria, ATP receptors have themselves been placed into distinct pharmacological subclasses (Burnstock & Kennedy 1985), and electrophysiological studies have shown that ATP can activate both G protein-coupled receptors that signal through the elaboration of cytoplasmic second messengers (metabotropic receptors) (O'Connor et al 1991) and ligand-gated channels that mediate direct and rapid increases in membrane ion conductance (ionotropic receptors) (Bean 1992).…”
Section: Introductionmentioning
confidence: 99%